Mechanical Stress Modulates the RANKL/OPG System of Periodontal Ligament Stem Cells via α7 nAChR in Human Deciduous Teeth: An In Vitro Study. (2nd May 2019) - Chen, Yujiang; Yang, Kuan; Zhou, Zhifei; Wang, Lulu; Du, Yang; Wang, Xiaojing
Abstract : The aim of this study was to investigate the mechanism by which periodontal ligament stem cells (PDLSCs) modulate root resorption of human deciduous teeth under mechanical stress. In this investigation, the PDLSCs were derived from deciduous and permanent teeth at different stages of root resorption. A cyclic hydraulic pressure was applied on the PDLSCs to mimic chewing forces in the oral environment. The cultured cells were characterized using osteogenic and adipogenic differentiation assays, quantitative real-time polymerase chain reaction (qRT-PCR), and Western blotting analysis. The PDLSCs exhibited the ability to induce osteoclast differentiation under certain mechanical stresses. As the expressions of RUNX2, alkaline phosphatase (ALP), and osteoprotegerin (OPG) were significantly reduced, the receptor activator of the nuclear factor kappa-B ligand (RANKL) was upregulated increasing the RANKL/OPG ratio. Under hydrodynamic pressure at 0-135 kPa, the expressions of alpha 7 nicotinic acetylcholine receptors ( α 7 nAChR), p-GSK-3 β, and active- β -catenin were markedly upregulated in PDLSCs from unresorbed deciduous teeth. Treatment with the α 7 nAChR inhibitor alpha-bungarotoxin ( α -BTX) and the Wnt pathway inhibitor DKK1 may reverse the mechanical stress inducing upregulation of RANKL and reduction of RUNX2, ALP, and OPG. Alizarin red staining confirmed these results. The mechanical stress applied on the deciduous tooth PDLSCs can induce osteoclastic effects through upregulation of α 7 nAChR and activation of the canonical Wnt pathway. It can be suggested that chewing forces may play a major role at the beginning of the physiological root resorption of deciduous teeth.